2007
DOI: 10.2118/07-12-tn1
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Fluid Leak-off in Naturally Fractured Gas Fields and Its Effects on Fracture Geometry

Abstract: In investigations of tectonic stress fields, natural fractures are often found in low-permeability formations. Fracturing wells in naturally fractured gas fields can differ dramatically from those in conventional isotropic formations. Fluid leak-off is the pri-mary difference. To take account of fracturing fluid leaking into the formation through natural fractures and the matrixes, this paper presents a new model that describes fluid leak-off in naturally fractured gas fields and its exact solution is given by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…This large difference could be Furthermore, the calculated flow velocity is between 0.02 cm/s and 0.07 cm/s. Compared to values given by Yi and Peden [46] and Li et al [24], which range from 1 × 10 −3 m/min to 2 × 10 −3 m/min and 2 × 10 −5 m/min to 5 × 10 −5 m/min, respectively, the leak-off velocity in this paper is several orders of magnitude larger. This large difference could be due to two main reasons as low fracturing fluid viscosity and high-pressure difference.…”
Section: Model Validationcontrasting
confidence: 72%
See 2 more Smart Citations
“…This large difference could be Furthermore, the calculated flow velocity is between 0.02 cm/s and 0.07 cm/s. Compared to values given by Yi and Peden [46] and Li et al [24], which range from 1 × 10 −3 m/min to 2 × 10 −3 m/min and 2 × 10 −5 m/min to 5 × 10 −5 m/min, respectively, the leak-off velocity in this paper is several orders of magnitude larger. This large difference could be due to two main reasons as low fracturing fluid viscosity and high-pressure difference.…”
Section: Model Validationcontrasting
confidence: 72%
“…This large difference could be due to two main reasons as low fracturing fluid viscosity and high-pressure difference. The fracturing fluid viscosity in our experiment was 10 mPa•s, and in the study by Li et al [24] was 400 mPa•s. Pressure differences were almost 2.069 MPa and 6 MPa in the two studies, which reached up to 40 MPa in this work.…”
Section: Model Validationsupporting
confidence: 47%
See 1 more Smart Citation
“…Te authors concluded that the fracture is central to the permeability of hydrocarbons and that the fuid fows from the matrix to the fracture depending on the geometric parameters of the fracture such as permeability and porosity [18]. Li et al [19] extended the study of fuid leakage in areas of tectonic stress. To examine this, the tectonic movements afected the fracture behavior, which causes losses in the fuids of low-permeability formations.…”
Section: Introductionmentioning
confidence: 99%